High power fiber laser system for a high repetition rate laserwire - Nevay, L; Walczak, R; Corner, L (American Physical Society, 2014)
We present the development of a high power fiber laser system to investigate its suitability for use in a transverse electron beam profile monitor, i.e., a laserwire. A system capable of producing individual pulses up to 165.8±0.4μJ at 1036 nm with a full width at half maximum of 1.92±0.12ps at 6.49 MHz is demonstrated using a master oscillator power amplifier design with a final amplification stage in a rod-type photonic crystal fiber. The pulses are produced in trains of 1 ms in a novel burst mode amplification scheme to match the bunch pattern of the charged particles in an accelerator. This method allows pulse energies up to an order of magnitude greater than the steady-state value of 17.0±0.6μJ to be achieved at the beginning of the burst with a demonstrated peak power of 25.8±1.7MW after compression. The system is also shown to demonstrate excellent spatial quality with an M2=1.26±0.01 in both dimensions, which would allow nearly diffraction limited focusing to be achieved. © 2014 Published by the American Physical Society.